Russia-NATO Strategic Rivalry and Influence Struggle in Eastern Europe in Security and Economy - Syaiful Rohman; Marthen Napang; Siti Nurhasanah (UIN Sunan Gunung Djati, 2021)
Global powers such as NATO, European Union, China and Russia have different characteristics and interests in world politics. Russia after Soviet Union tends to be in a relatively weak position in terms of influence, security and economy. Today Russia's relations with the European Union and the United States have improved after the Cold War. In recent years, Russia and NATO have not only strengthened the economy and security related to the military, but have gone so far as to strengthen the influence of its main State in Eastern Europe. This study will analyze Russia's political policies towards NATO and Eastern Europe from the perspective of security and economic interests. The method used is qualitative by conducting an in-depth study of the data obtained from the results of previous research. The results of this study indicate that Russia and NATO are involved in competing for strategic influence in Eastern Europe, especially Ukraine and the former Soviet Union. Russia and NATO, which is sponsored by the United States, are trying to achieve their respective interests by making efforts to increase strength which includes political, security and economic.